Economic security of regions: A prerequisite for diversifying the Azerbaijan economy - Aliyev, Shafa; Babayev, Farid; Galandarova, Ummuhabiba; Gafarli, Galib; Balajayeva, Tahmina (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This article aimed to empirically substantiate the development of priority sectors to improve the economic security of the regions in Azerbaijan to achieve the goals of diversifying the national economy. We calculated an integral indicator of the economic security of areas by combining various socioeconomic development indicators, accounting for their variations from 2005 to 2022. The research established the relationship between the integral indicator of economic security in Azerbaijan’s regions and the availability and efficiency of production factors in critical sectors of the economy, including Mining and quarrying, Manufacturing, Construction, Agriculture, forestry and fishing, and Trade. By applying the regression method, we concluded that agriculture and trade play a decisive role in increasing regional economic security in modern conditions. The research highlighted those growing factors: the number of employees, wages, and investments in fixed assets in these sectors, would be instrumental in achieving the adequate diversification of the country’s economy.